Le sexe du militantisme - Fillieule, Olivier; Roux, Patricia (Presses de Sciences Po, 2009)
Le sexe du militantisme propose une analyse de la (re)production des rapports de pouvoir au travers des pratiques militantes, saisissant les logiques par lesquelles les inégalités de genre, de classe et de race imprègnent le militantisme, qu'il soit de gauche ou de droite, progressiste ou conservateur. Premier ouvrage en français à explorer le militantisme dans une perspective de genre à partir de recherches empiriques sur les partis, les syndicats et les mouvements sociaux, il rassemble des politistes, sociologues, anthropologues et historiennes dont le souci est de ne pas appréhender les luttes politiques comme si elles étaient « neutres » et non sexuées. Une contribution majeure à l'étude des mobilisations collectives qui complète les analyses classiques, aveugles aux rapports de genre.
Keywords: LGBTQIA2+; amérique du nord; amérique latine; amériques; anarchisme; anthropologie; approches et analyses; asie; canada; caraïbes; discipline; europe; france; genre; guyane française; histoire; hétérosexisme; identités LGBTQIA2+; inégalités; israël; italie; militance; mouvements sociaux; patriarcat; québec; racisme; rapports sociaux; rapports sociaux de sexe; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences humaines; sociologie; syndicat; système colonial; systèmes d'oppressions; thématiques; violences

Looking for Asian butch-dykes: Exploring filmic representations of east Asian butch-dykes in Donna Lee's Enter the mullet - Lin, Hui-Ling (Journal of Lesbian Studies, 2009)
Asian butch-dykes have been overlooked in analyses of Chinese cinema, studies that often concentrate on “feminized” transgender roles. This article examines cinematic representations of Asian butch-dykes through film analysis of Enter the Mullet (2004), a five minute short, and in-depth interviews with the filmmaker, Donna Lee, a Chinese-Canadian in Vancouver. Lee’s film is inspired by Enter the Dragon (1973), starring Bruce Lee, the most recognized icon of Asian masculinity. Combining with the mullet hairstyle, which is often associated with White working-class, the filmmaker introduces viewers to the hybrid masculinity of Asian butch-dykes. The article argues that Asian female masculinity can be a strategic means of destabilizing the hegemony of White–male–middle-class masculinity
Keywords: amériques; approches et analyses; asie; canada; chine; identités LGBTQIA2+; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions

Ru - Thúy, Kim (Libre Expression,une compagnie de Quebecor Media, 2009)
« "Le paradis et l'enfer s'étaient enlacés dans le ventre de notre bateau. Le paradis promettait un tournant dans notre vie, un nouvel avenir, une nouvelle histoire. L'enfer, lui, étalait nos peurs : peur des pirates, peur de mourir de faim, peur de s'intoxiquer avec les biscottes imbibées d'huile à moteur, peur de manquer d'eau, peur de ne plus pouvoir se remettre debout, peur de devoir uriner dans ce pot rouge qui passait d'une main à l'autre, peur que cette tête d'enfant galeuse ne soit contagieuse, peur de ne plus jamais fouler la terre ferme, peur de ne plus revoir le visage de ses parents assis quelque part dans la pénombre au milieu de ces deux cents personnes." Ru est le récit d'une réfugiée vietnamienne, une boat people dont les souvenirs deviennent prétexte tantôt à l'amusement, tantôt au recueillement, oscillant entre le tragique et le comique, entre Saigon et Granby, entre le prosaïque et le spirituel, entre les fausses morts et la vraie vie. »-- Quatrième de couverture.
Keywords: amériques; approches et analyses; arts; asie; boat people; canada; cours; discipline; histoire et politique; immigration; lit3220; littérature; premier cycle; québec; roman; régions géographiques; système colonial; systèmes d'oppressions; thématiques; vietnam; écriture des femmes*; études littéraires

Sexual Attitudes and Double Standards: A Literature Review Focusing on Participant Gender and Ethnic Background - Fugère, Madeleine A.; Escoto, Carlos; Cousins, Alita J.; Riggs, Matt L.; Haerich, Paul (Sexuality & Culture : An Interdisciplinary Quarterly, 2008)
We conducted a review of literature regarding sexual attitudes and double standards, focusing on participant gender and ethnic background. We found that men had more permissive sexual attitudes than women, and that African Americans had the most permissive sexual attitudes, followed by White Americans, then by Hispanic Americans and Asian Americans. The literature regarding sexual double standards was mixed; some studies showed evidence of continued sexual double standards and some studies showed the absence of sexual double standards. In some studies, men were more likely to endorse the sexual double standard than women. We found only one article addressing sexual double standards using ethnic background as a quasi-independent variable; this research revealed that non-North American (Russian and Japanese) samples were more likely to endorse the traditional double standard, that sex is more acceptable for men than for women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; cours; discipline; europe; japon; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; russie; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques; états-unis

A new Vision for advancing our movement for reproductive health, reproductive rights and reproductive justice - Asian Communities for Reproductive Justice (Asian Communities for Reproductive Justice, 2005)
Forward Together’s (then Asian Communities for Reproductive Justice or ACRJ) groundbreaking analysis of the framework and vision for reproductive justice, described by organizations and funders as revelatory and pivotal to the field.
Keywords: amériques; approches et analyses; asie; droits des femmes*; femmes* asiatiques; femmes* de couleur; inégalités; justice reproductive; justice sociale; militance; racisme; ressource en ligne; régions géographiques; santé; santé reproductive; sexisme; sexualité; systèmes d'oppressions; thématiques; éducation sexuelle; états-unis

La démocratie et le statut des femmes au Liban - Bdeir, Leila (Université du Québec à Montréal, 2005)
Keywords: IREF; approches et analyses; asie; discipline; femmes* politiques; liban; militance; mouvements féministes; mémoires/thèses; régions géographiques; science politique; science politique et droit; sexisme; systèmes d'oppressions; thématiques

Pour une théorie générale de l'exploitation. Deuxième partie: repartir du bon pied - Delphy, Christine (Mouvements, 2004)
Keywords: OFDIG; afrique; amériques; approches et analyses; asie; cours; cycles supérieurs; discipline; discours dominant; exploitation; fem9000; intersectionnalité; marxisme; ressource en ligne; régions géographiques; sciences de la gestion; systèmes d'oppressions; thématiques; travail; violences; économie; économie sociale

Rocking Sexualities: Iranian Migrants' Views on Sexuality - Ahmadi, Nader (Archives of Sexual Behavior : The Official Publication of the International Academy of Sex Research, 2003)
The purpose of this article is to put forward a theoretical discussion about Islamic views of sexuality and by means of an example show how Iranian immigrants in Sweden view sexuality and sexual culture. Building on theories that compare individualistic and holistic ways of thinking, the article seeks to elucidate the impact of basic cultural qualities on the formation of sexualities. The conclusion of the article is that the encounter with the Swedish way of thinking and the Swedish sexual culture seems to have influenced Iranian migrants' views on the nature of the relationship between couples and sexual decision making within the relationship. Exposed to an individualistic ideology and lifestyle in Sweden, Iranian migrants show a clear tendency to revise their previous holistic way of thinking, especially in regard to sexuality: the traditional, authoritarian, patriarchal sexual relationship among Iranian migrants in Sweden is giving way to more egalitarian relationships, and a relatively strong tendency towards a similarity of views between the sexes regarding sexuality can be observed. The most important change that could be observed in regard to the respondents in the study is probably an increased individualism.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; asie; cours; discipline; europe; inégalités; iran; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexualité; suède; systèmes d'oppressions; thématiques; travail social

"You Can Never Be Too Rich or Too Thin": Popular and Consumer Culture and the Americanization of Asian American Girls and Young Women - Lee, Stacey J.; Vaught, Sabina (The Journal of Negro Education, 2003)
First- and second-generation youth of color are vulnerable to racialized images of gender and sexuality as reflected in and perpetuated by dominant forms of popular and consumer cultures. These popular images inform the process of Americanization, including racialized sexualization, for first- and second-generation Americans. This paper examines the way first- and second-generation Asian American girls and young women interpret and reinterpret popular representations of their positions in the United States. Data from two qualitative studies on Asian American young women will be presented.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; corps; cours; discipline; féminisme pop; hmong; intersectionnalité; laos; premier cycle; périodes historiques; racisme; représentation des femme*; représentation des femmes* racisées; ressource en ligne; régions géographiques; sciences de l'éducation; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis

Mousson de femmes - Perrin, Elula (La Cerisaie, 2003)
Récit d'un amour passionné entre deux femmes en Indochine pendant la Seconde Guerre mondiale. Elula Perrin, née à Hanoi en 1929, témoigne de la terreur et des tueries perpétrées en Indochine entre 1945 et 1946.
Keywords: 1900-1999; 1940-1949; approches et analyses; asie; guerre; mémoire collective; personnes lesbiennes; périodes historiques; roman; régions géographiques; système colonial; systèmes d'oppressions; thématiques; vietnam; violences

Enjeux contemporains du féminisme indien - Haase-Dubosc, Danielle (Éditions de la Maison des sciences de l'homme, 2002)
Pour la première fois en français, un recueil d'essais témoigne des luttes et de la politique féministes en Inde, dans un contexte bien différent des problématiques occidentales. Inscrits dans la période contemporaine, de la turbulence des années 1960 et 1970 aux défis des années 1990, certains de ces textes ont été rédigés à chaud, d'autres sont plus rétrospectifs. Ils constituent un ensemble original à travers six grandes rubriques qui se complètent et se répondent l'une l'autre ... Tout en présentant les expériences historiques particulières qui ont nourri les théories et les pratiques du mouvement des femmes en Inde, cet ouvrage présente une approche vivante et engagée des questions actuellement en jeu pour les femmes indiennes.une vision plurielle du féminisme , dans une perspective transnationale respectueuse de l'altérité historique et culturelle
Keywords: 1900-1999; 1960-1969; 1970-1979; approches et analyses; asie; conflit; cours; cycles supérieurs; droits des femmes*; fem1000; fem7000; histoire des femmes*; histoire et politique; inde; inégalités; lit3220; mouvements des femmes*; premier cycle; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques

« Sex and the City » : la prostitution à l’ère des migrations mondiales - Robinson, Lillian S. (Recherches féministes, 2002)
Comme caractéristique du développement capitaliste, la migration économique a toujours entraîné le travail sexuel. À l’heure de la mondialisation, cela signifie pour beaucoup de femmes, qui émigrent du village à la grande ville dans leur propre pays ou du pays natal à l’étranger, un choix imposé par les circonstances. Cet article examine surtout la décision d’émigrer, les moyens empruntés et la situation à l’étranger de celles - la grande majorité, d’ailleurs -- qui n’ont pas été victimes d’un trafic, mais qui ont exercé ce choix imposé. Le rôle dans l’émigration des travailleuses sexuelles et des clients « émigrés » en tant que touristes sexuels fait partie de la discussion, ainsi que d’autres caractéristiques économiques et culturelles.Summary As a feature of capitalist development, economic migration has historically entailed sex work as one of its components. In the age of globalization, this means a forced choice for many women, as they move from the village to the city in their own countries and across international borders. The present article focuses on the decision making process, the means of migration, and the experience in the urban site, national or international, of those -- the vast majority -- who have not been "trafficked", but have made this forced choice their life strategy. The impact on sex worker migration of customer "migration" in the form of sex tourism is discussed, along with the other economic and cultural factors.
Keywords: 1900-1999; afrique; amériques; approches et analyses; asie; capitalisme; cours; discipline; droits des femmes*; europe; féminisme du sud; féminisme décolonial; globalisation; his4860; histoire et politique; immigrantes clandestines; immigration; inde; industrie du sexe; inégalités; migration; pauvreté; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; sciences sociales; sexisme; sociologie; système colonial; systèmes d'oppressions; thématiques; tourisme sexuel; travail; travail des femmes*; travail du sexe

Doing fieldwork on women in theocratic Islamic states: A critique of the politics of empiricism - Mojab, Shahrzad (Resources for Feminist Research, 2001)
This paper examines the way some feminist advocates of cultural relativism adopt positivism and empiricism in order to discredit the radical critique of Islamization of gender relations in Iran. It argues that relativists use the positivist/empiricist cult of experience and objectivity in order to undermine the critique of policies and practices that oppress the women of Iran. The choice of a method of inquiry is not based on methodological considerations only. The researcher's political preferences, implicit or explicit, plays a significant role in the entire research process, especially in the study of sensitive issues. Although one may identify a methodological tradition with a certain brand of politics, the paper argues that methodological paradigms enter into changing relationships with structures of power.
Keywords: approches et analyses; asie; cours; discipline; discours dominant; fem1000; iran; méthodologie; premier cycle; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; épistémologie